PENGAWASAN SATUAN POLISI PAMONG PRAJA KABUPATEN INDRAGIRI HULU DALAM PENCEGAHAN PENAMBANG EMAS ILEGAL DI KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Ayu, Febrina Fitri (UIR PRESS, 2020)
This study aims to determine how the Supervision of Indragiri Hulu Regency Civil Service Police Unit in the prevention of Illegal Gold Miners in Batang Peranap Subdistrict and Indragiri Hulu District and determine the obstacles faced by unscrupulous Satpol PP members in handling Illegal Gold Miners in Batang Peranap District. This type of research which is located in the Civil Service Police Unit precisely in the District Office of Batang Peranap District uses qualitative methods, namely a study that makes humans an instrument and adapted to the reasonable situation in relation to data collection which is generally qualitative in nature and is a procedure research that produces descriptive data in the form of written or oral words from people and observable behavior. Determination of informants in this study using purposive sampling technique. Purposive sampling is a sampling technique for data sources with certain considerations that the data source is considered to know the most about what is expected, making it easier for researchers to explore objects or social situations that are being studied. Data collection techniques used consisted of observations, interviews and documentation. Based on the technical analysis above, the researcher assessed and concluded that the supervisory role of the Indragiri Hulu civil service police unit in preventing illegal gold miners in the Batangapap subdistrict still lacked the role and lack of firmness by the Satpol PP, the Police and the TNI in handling the case so that there were still many who violating these regulations. This can occur because there are still obstacles that still interfere with the performance of the Satpol PP, such as lack of public awareness, insufficient regulations, and a lack of oversight by the Satpol PP and the Police.